(untitled) (Journal of Parents and Teachers, 2023)
Diversity requires that educational centers offer a response to that need. It is a reality that is imposed, therefore an inalienable demand. It is key to work on teachers’ sensitivity to this reality, led by those who understand inclusion from equal opportunities. as well as the understanding of families and coordination with the administration. With students the process is much more natural.